Industrial Training Report: Shizuoka Library MARA Japan Industrial Institute (MJII) / Fatin Nurain Baharuddin - Baharuddin, Fatin Nurain (Faculty of Information Management, 2016)
This industrial report training consist of industrial activities of student within 5 month of internship at Shizuoka Library, Mara Japan Industrial Institute (MJII). This report will consist of 4 different chapters. Basically the four chapter cope the information of the training activities. First chapter will an introduction of the organization where its cope the story of information background and organizational structure. Second chapter then will explained about the departmental structure within the organizational with their functions. The third and fourth chapter are the most crucial part where this part explaining all industrial training activities and the training reflection from the perceptiveness of student. Chapter three will explained and discussed in detailed about the training activity that students had perform and also the special project that they have carried out. In chapter four, student then will discussed on overall reflection of the training activities from the specific view. The closer will be the conclusion, reference and attachment of appendices.